Temperature dependent raman spectroscopy and sensing behavior of few layer SnSe2nanosheets - Pawbake, Amit S.; Date, Abhijit; Jadkar, Sandesh R.; Late, Dattatray J. (Chemistryselect, 2016)
Two- dimensional (2D) tin diselenide (SnSe2) nanosheets were synthesized using solvothermal route in one step and perform its humidity sensing, photo sensing and temperature dependant Raman spectroscopy studies. The sensor devices based on few layer SnSe2 nanosheets were prepared and which shows fast response as well as recovery time along with good long-term stability and high sensitivity. The photo sensing behavior shows the typical response time and recovery time to be similar to 310 ms and similar to 340 ms respectively for visible light illumination. The room temperature humidity sensing behaviors were studied in the range of 11-97% relative humidity (RH). The ob-served sensitivity of similar to 81% with response time of similar to 74 sec and recovery time of similar to 30 sec were calculated for the few layer SnSe2 nanosheets based humidity sensor. The humidity sensing results confirms the high stability of the device even after six months of time. The temperature dependent Raman spectroscopy investigation in the range of 80 K to 593 K were carried out which shows the negative temperature coefficient and softening of Raman modes as we increases the temperature. The softening modes of SnSe2 nanosheets due to temperature were explained on the basis of a double resonance process which is more active in an atomically thin sample.